MOISTURE SAVING METHODS AND TECHNOLOGIES IN ORENBURG AGRICULTURE - N. A. Maksyutov; V. M. Zhdanov; V. Yu. Skorokhodov; Yu. V. Kaftan; D. V. Mitrofanov; N. A. Zenkova; V. N. Zhizhin (Зерновое хозяйство России, 2018)
The article gives a review of published material concerning principal methods of spring moisture accumulation in soil in dry conditions of Orenburg and other regions of the South-East. Such review is of great importance because of frequently recurring drought, especially in a spring-summer period of the last years. In such years spring moisture accumulations in soil can play a crucial role in the struggle with drought.  But a lot of methods and technologies of moisture accumulations are not used, that significantly reduces the yields. The article shows the results of long-term trails during four crop rotations, where we studied bare (weedfree) fallow, natural fallow, green fallow for winter and spring durum wheat in the system of 6-field crop rotations. During the years we determined the dynamics of soil moisture in fallow lands in the periods from its beginning to the sowing of winter and spring durum wheat. It has been estimated the effect of different types of fallow on soil consumption of moisture from snow during its melting. The article presents the data about the productivity of spring durum wheat in dependence on fallow and non-fallow ancestors and nutrition on average in 24 years. We have made some conclusions on the basis of the review and results of the trials.